# -22=8y+6(y+8)

## Simple and best practice solution for -22=8y+6(y+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -22=8y+6(y+8) equation:

Simplifying
-22 = 8y + 6(y + 8)
Reorder the terms:
-22 = 8y + 6(8 + y)
-22 = 8y + (8 * 6 + y * 6)
-22 = 8y + (48 + 6y)
Reorder the terms:
-22 = 48 + 8y + 6y
Combine like terms: 8y + 6y = 14y
-22 = 48 + 14y
Solving
-22 = 48 + 14y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-14y' to each side of the equation.
-22 + -14y = 48 + 14y + -14y
Combine like terms: 14y + -14y = 0
-22 + -14y = 48 + 0
-22 + -14y = 48
Add '22' to each side of the equation.
-22 + 22 + -14y = 48 + 22
Combine like terms: -22 + 22 = 0
0 + -14y = 48 + 22
-14y = 48 + 22
Combine like terms: 48 + 22 = 70
-14y = 70
Divide each side by '-14'.
y = -5
Simplifying
y = -5